(untitled) (International relations and international law Journal, 2025)
This article examines the application of the «soft power» concept using the case of France and analyzes the potential for its adaptation by the countries of Central Asia, taking into account the specific socio-political and cultural contexts of the region. Special attention is given to the key instruments of French soft power, including cultural diplomacy, tourism promotion, educational programs, student exchange initiatives, national branding development, support for creative industries, and the organization of international cultural events. These elements contribute significantly to strengthening France’s positive and sustainable image on the global stage. The empirical basis of the study consists of the results of a sociological survey conducted among students, postgraduate students, young professionals, and international relations experts from Kazakhstan, Kyrgyzstan, Uzbekistan, and Tajikistan. The methodology of the research includes content analysis, comparative analysis, and statistical data processing. The findings reveal that France is primarily perceived in the region as a reliable cultural and educational partner, while its political and economic influence remains relatively limited. The authors conclude that there is a need to diversify the tools of soft power, placing greater emphasis on the expansion of educational partnerships, the development of tourism, support for creative industries, and the strengthening of cultural dialogue. Enhancing these areas could open new prospects for deepening cooperation between France and the countries of Central Asia across multiple sectors. Key words: soft power, cultural diplomacy, France, Central Asia, national branding, tourism.